Effects of Stance Width and Barbell Placement on Kinematics, Kinetics, and Myoelectric Activity in Back Squats - Larsen, Stian; Kristiansen, Eirik; Helms, Eric; van den Tillaar, Roland (Frontiers in Sports and Active Living, 2021)
Barbell placement and stance width both affect lifting performance in the back squat around the sticking region. However, little is known about how these squat conditions separately could affect the lifting performance. Therefore, this study investigated the effects of stance width and barbell placement upon kinematics, kinetics, and myoelectric activity around the sticking region during a three-repetition maximum back squat. Nine men and nine women (body mass: 76.2 ±11.1, age: 24.9 ± 2.6) performed back squats with four different techniques, such as: high-bar narrow stance (HBNS), high-bar wide stance, low-bar narrow stance, and low-bar wide stance where they lifted 99.2 ± 23.6, 92.9 ± 23.6, 102.5 ± 24.7, and 97.1 ± 25.6 kg, respectively. The main findings were that squatting with a low-bar wide stance condition resulted in larger hip contributions to the total moment than the other squat conditions, whereas squatting with an HBNS resulted in greater knee contributions to the total moment together with higher vastus lateralis and less gluteus maximus myoelectric activity. Our findings suggest that training with an HBNS could be beneficial when targeting the knee extensors and plantar flexors, whereas a low-bar wide stance could be beneficial when targeting the hip extensors.